The Role of Electrical Impedance Tomography for Management of High-Risk Pulmonary Embolism in a Postoperative Patient - Wang, Xinchen; Zhao, Hua; Cui, Na (Frontiers in Medicine, 2021)
Electrical impedance tomography (EIT) is a non-invasive, radiation-free and bedside imaging tool that is widely used for real-time monitoring of lung ventilation. Recently, it has been proposed for use in quantitative assessment of regional lung perfusion with hypertonic saline bolus injection and consequently for pulmonary embolism (PE) detection. Here, we present a case of high-risk PE in a postoperative patient, in which EIT monitoring provided us with useful information for diagnosis and decision-making, especially with the challenge of anticoagulation and risk of bleeding.